CNS organoids: an innovative tool for neurological disease modeling and drug neurotoxicity screening. Issue 2 (February 2020) - Chhibber, Tanya; Bagchi, Sounak; Lahooti, Behnaz; Verma, Angela; Al-Ahmad, Abraham; Paul, Manash K.; Pendyala, Gurudutt; Jayant, Rahul Dev
Highlights: 3D CNS organoids share architecture and functions resembling the human brain. Recapitulating key features of the early-stage brain under a controlled microenvironment. Modeling tool to study CNS drug development, toxicity and personalized screening. Mimicking the human brain physiology to study unique neurodevelopmental disorders. Abstract : The paradigm of central nervous system (CNS) drug discovery has mostly relied on traditional approaches of rodent models or cell-based in vitro models. Owing to the issues of species differences between humans and rodents, it is difficult to correlate the robustness of data for neurodevelopmental studies. With advances in the stem-cell field, 3D CNS organoids have been developed and explored owing to their resemblance to the human brain architecture and functions. Further, CNS organoids provide a unique opportunity to mimic the human brain physiology and serve as a modeling tool to study the normal versus pathological brain or the elucidation of mechanisms of neurological disorders. Here, we discuss the recent application of a CNS organoid explored for neurodevelopment disease or a screening tool for CNS drug development.